What is Academic Freedom? A Century of Debate, 1915-Present - Gordon, Daniel (Taylor & Francis, 2022)
This book explores the history of the debate, from 1915 to the present, about the meaning of academic freedom, particularly as concerns political activism on the college campus. The book introduces readers to the origins of the modern research university in the United States, the professionalization of the role of the university teacher, and the rise of alternative conceptions of academic freedom challenging the professional model and radicalizing the image of the university. Leading thinkers on the subject of academic freedom-Arthur Lovejoy, Angela Davis, Alexander Meiklejohn, Edward W. Said, among others-spring to life. What is the relationship between freedom of speech and academic freedom? Should communists be allowed to teach? What constitutes unacceptable political "indoctrination" in the classroom? What are the implications for academic freedom of creating Black Studies and Women's Studies departments? Do academic boycotts, such as those directed against Israel, violate the spirit of academic freedom? The book provides the context for these debates. Instead of opining as a judge, the author discloses the legal, philosophical, political, and semantic disagreements in each controversy. The book will appeal to readers across the social sciences and humanities with interests in scholarly freedom and academic life.